The Relationship between Transformational Leadership Style, Innovation and Performance in Egyptian SMEs - Garhy, Mohamed; Hassan, Rawya; Khedr, Wessam (The Arab Journal of Administration, 2019)
This study investigates the impact of transformational leadership style on both the processes Innovation and innovative Performance, as well as testing the moderating effects of Innovative Culture in those relationships. Paired data were gathered from 76 senior managers and 209 employees in 76 Egyptian small and medium enterprises(SMEs). The research used Structural Equation Model method to determine the best path for the relationship under investigation. Although the results did not support the first and second hypotheses that tested the direct relationship between transformational leadership style and processes innovation and innovative performance, respectively, however, the third and fourth hypotheses were supported, confirming the role of innovative culture as a moderator on the relationship between transformational leadership style and each of processes innovation and innovative performance variables. The study recommended that managers should be trained on transformational leadership skills as part of the administrative development plans, to achieve innovation and long-term performance by creating an innovative culture in the organization. The study also recommended that the government should provide more support to small and medium enterprises to encourage more innovative initiatives.